Rust in Plumeria spp. (Apocynaceae) in the State of Mato Grosso do Sul, Brazil. - de Carvalho, Cassia; Lemes, Camila Soares Rosa; Sorgato, José Carlos; Gavassoni, Walber Luiz; Bacchi, Lilian Maria Arruda; Hirata, Lucia Mayumi (Ornamental Horticulture, 2014)
Frangipani (Plumeria spp.) is a plant widely used in urban ornamentation, due to its hardiness, easy handling and exuberance of its flowers. Plumeria spp. Leaves were collected in Dourados, MS, Brazil, with typical symptoms and signs of the presence of rust: powdery yellowish uredinias in the abaxial and chlorotic and necrotic spots on the adaxial surface of the leaves, sometimes resulting in leaf abscission. The present study aims to record the occurrence of the disease in the State of Mato Grosso do Sul. Microscopic observations and measurements of uredinospores and teliospores confirmed that the fungus infecting plants was Coleosporium plumeriae.